Bringing Reflections into the TEFL Classrooms - M Sri Samiati Tarjana (TEFLIN, 2002)
Abstract: Reflective practice is defined by John Dewey as a proactive, ongoing examination of beliefs and practices, their origins and impacts. In the reflective practice, the teacher and learners are engaged in a continuous cycle of self-observation and self-evaluation in order to understand their own actions and reactions, and thereby develop the teaching-learning process on an on-going basis. While English is regarded as compulsory in the preparation of more qualified human resources for the country, there are still complaints about the low English mastery of the majority of secondary and tertiary education graduates in Indonesia. It seems likely that bringing the reflective practice in the TEFL classrooms will help improve the teaching-learning of English in a more caring and responsive manner. It is expected that this will not only improve the English mastery, but also develop personal talents and capacities of the learners. The features of reflective practice in TEFL and their advantages for personal and professional development will be further discussed.